THE STRUCTURE OF MIXED SURFACTANT MONOLAYERS AT THE AIR-LIQUID INTERFACE, AS STUDIED BY SPECULAR NEUTRON REFLECTION - Penfold, J; Thomas, R; Simister, E; Lee, E; Rennie, A (1990)
The specular reflection of neutrons is now finding widespread application in the study of a range of problems in surface chemistry. In recent studies, using hydrogen-deuterium contrast variation, it has been possible in the investigation of surfactant adsorption at the air-liquid interface to determine both the surfactant surface excess and the detailed surface structure of the surfactant molecules. The authors present results that extend these studies to the adsorption of mixed surfactants at the air-liquid interface. For the mixed system sodium dodecyl sulphate and dodecanol, they have determined the surface excess and surface structure of each component in the mixed surface layer.